2002
DOI: 10.1007/s15010-002-2023-3
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk for Hepatitis A and Hepatitis E among Health Care Professionals?

Abstract: Specific departments of health care show higher prevalence of anti-HAV or anti-HEV. In the case of HEV further studies in the exposed working field are needed. Since no connection between the two serological results was found, transmission mechanisms might be (partly) different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…While Trautwein et al [33] determined an overall seroprevalence of anti-HEV-IgG of 2.05% in German immigrants from the former UDSSR in 1995, in 1997 Jänisch et al [34] found 5.2% of long-term expatriates to be positive to anti-HEV-IgG and Nübling et al [35] investigated a rate of seropositivity to anti-HEV-IgG of 3.9 in 2002; our rate of seropositivity to anti-HEV-IgG exceeds this value nearly three times over. Whether the rising incidence is based on heightened clinical awareness and more frequent testing of possible cases or is caused by a real increase in the number of infections remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…While Trautwein et al [33] determined an overall seroprevalence of anti-HEV-IgG of 2.05% in German immigrants from the former UDSSR in 1995, in 1997 Jänisch et al [34] found 5.2% of long-term expatriates to be positive to anti-HEV-IgG and Nübling et al [35] investigated a rate of seropositivity to anti-HEV-IgG of 3.9 in 2002; our rate of seropositivity to anti-HEV-IgG exceeds this value nearly three times over. Whether the rising incidence is based on heightened clinical awareness and more frequent testing of possible cases or is caused by a real increase in the number of infections remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, haemodialysis patients in four different studies [57,[96][97][98], those who had undergone minor surgery and abdominal surgery in Spain [4], healthcare workers in emergency admission and surgery in Germany [99] and male prisoners and drug treatment patients in Denmark [56] were found to have a higher anti-HEV IgG prevalence than the reference group.…”
Section: Potential For Parenteral Transmissionmentioning
confidence: 99%
“…Seroprevalence of hepatitis A virus antibody among healthcare workers[32][33][34][35][36][37][38][39][40][41][42][43][44][45][47][48][49][50] …”
mentioning
confidence: 99%